2009
DOI: 10.1159/000245063
|View full text |Cite
|
Sign up to set email alerts
|

BMP-7 Blocks the Cyclosporine-A-Induced Epithelial-to-Mesenchymal Transition in Renal Tubular Epithelial Cells

Abstract: Aims: The nephrotoxic side effects of cyclosporine A (CsA) are partly due to induction of the epithelial-to-mesenchymal transition (EMT), possibly through upregulation of connective tissue growth factor (CTGF). Bone morphogenetic protein (BMP-7) has been reported to protect against and reverse renal injury via its renotropic and antifibrotic effects. We therefore designed a method to investigate the mechanism by which BMP-7 inhibits CSA-induced EMT in cultured human renal proximal tubular epithelial (HK-2) cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 40 publications
(27 reference statements)
3
48
0
4
Order By: Relevance
“…[5][6][7][8] TGF-β 1 is a fibrogenic growth factor contributing to the mechanisms underlying EMT. 12,13) Although TGF-β 1 has been reported to be involved in many cellular signaling pathways, there has been recent interest in the roles of RhoA and ROCK as mediators of some of the actions of TGF-β 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] TGF-β 1 is a fibrogenic growth factor contributing to the mechanisms underlying EMT. 12,13) Although TGF-β 1 has been reported to be involved in many cellular signaling pathways, there has been recent interest in the roles of RhoA and ROCK as mediators of some of the actions of TGF-β 1 .…”
Section: Discussionmentioning
confidence: 99%
“…10,11) Transforming growth factor (TGF)-β 1 is an important fibrogenic growth factor known to play an important role in EMT development. 12,13) Although TGF-β 1 is thought to act via a number of cellular signaling pathways, connective tissue growth factor (CTGF) is a downstream target responsible for many of the pro-fibrotic effects of TGF-β 1 .…”
mentioning
confidence: 99%
“…These included TGF-β1, CTGF and BMP-7 (Zeisberg et al, 2003;Xu et al, 2009). The profibrotic cytokine TGF-β1 is a major contributor to TIF and nephropathy (Ling et al, 2003).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The pathogenesis of DN is complicated; renal fibrosis is the primary pathophysiologic process associated with chronic renal failure caused by DN (5). Epithelial-to-mesenchymal transition (EMT) and extracellular matrix (ECM) accumulation under pathological conditions also occur in mature tubular epithelial cells of the adult kidney, and have been implicated in renal interstitial fibrosis (6,7). It has previously been indicated that a large proportion of interstitial fibrosis cases originate from tubular epithelial cells via EMT in diseased kidneys (8).…”
Section: Introductionmentioning
confidence: 99%